The experimental study of the effect of screw and adhesive connection in the variation of cold-formed roof truss framing system - Santoso, Wilman Adi; Suswanto, Budi; Wahyuni, Endah; Komara, Indra (Institut Teknologi Sepuluh Nopember, 2018)
onnections with screws are used extensively to connect cold-formed steel (CFS) structural element, especially in the roof truss framing system. However, these connections cannot be relied upon to transfer loading due to the small thickness plates that result in more slender elements which are susceptible to local or distortional buckling and have low stiffness. Therefore, some improvements are made in this study by adding adhesive as the alternative connection. Three types of roof truss framing system are designed with a different connection, i.e. screw, adhesive and the combination of screw and adhesive. The study aims to investigate the behavior of frames connection through experimental studies with the given static load until the frame structure collapses, with attention to their initial (pre-slip) stiffness, elongation, and load-deformation capacity. As a result, the stiffness of adhesive connection given a lower value than screw connection. It is indicated of the delamination process, that the combination connection implied the better behavior with 50% screw reduction as well as increasing the load-deformation capacity with 69.7 mm, three times higher than the screw connection.